The Study of Students’ Dark language: Quality and reasons - Gh Rezvanian (مطالعات زبانی و بلاغی)
Language sociologists believed on the role of different non-linguistic factors, such as ethnicity, gender, education, social class, age, and geographical area in the emergence of linguistic forms. One of the social classes is the students’ stage which defined by its own discourse. But this study, with a study on the language of students, concludes that in the present situation, the role of these factors has changed, both because of the changes in global culture and the technological movement and cultural transformation of Iran in recent decades, which has been influenced by international developments and internal events and the collapse of past prehistory. Accordingly, based on the three variables of age, education, and gender and how they affect the language, which arranges the new power system in the language, and the convergence of these factors and the diminution of previously inflexible factors creates a new discourse that has a perfect expression in a language called "dark language". A language that has been spoken in secret in the past decade, but now appear. Then by the descriptive and explanatory study of this sublanguage, it concludes that this linguistic form, which expresses a certain style of life, confronts dominant ideology with a counter-crisis approach. It is not merely a moral phenomenon that is reformed with an advice and warning book, but a product of profound and complex socio-political variables.